Inovasi pembelajaran Pendidikan Agama Islam Berbasis ICT di Era Industri 4.0 - Ika Kartika; Saepudin Saepudin; Anandha Budiantoro; Sukarna Sukarna (Fakultas Tarbiyah IAI Nasional Laa Rooiba, 2023)
This research discusses Islamic Education Learning Innovations based on Information and Communication Technology (ICT) in the Industrial 4.0 era. The main focus of this research is on Islamic Religious Education learning innovations that rely on the use of Information and Communication Technology (ICT). The purpose of this study was to find out and analyze Islamic Religious Education learning innovations based on Information and Communication Technology (ICT) in the industrial era 4.0. The method used in this research is descriptive-analytical method. The literature study approach (Library research or also known as content analysis) is applied by conducting studies and analysis of primary sources such as books, scientific journals, articles and documents that are relevant to the discussion. The results of this study reveal that learning innovation based on Information and Communication Technology (ICT) is a concept and approach that is considered new by teachers in learning interactions, where they utilize ICT technology to facilitate the achievement of learning objectives through problem solving. The role of the teacher in developing innovation and learning media by utilizing ICT is an urgent need and a demand to increase the effectiveness of the learning process of Islamic Religious Education. Through learning interactions that utilize the internet network, the potential for creating more effective learning in Islamic Religious Education subjects can be realized. Keywords: Learning innovations in Islamic Religious Education, Information and Communication Technology in the era industry 4.0.